The impact of routine pmeumococcal conjugate immunisation on bacterial meningitis in Sowetan children-a time-series analysis - Hauptfleisch, Marc Peter Kedzlie (My University, 2013)
Introduction Invasive pneumococcal disease, including meningitis, caused by Streptococcus pneumoniae is a major cause of morbidity and mortality world-wide. The introduction of pneumococcal polysaccharide-protein conjugate vaccine (PCV) in the United States has resulted in a reduction in incidence of pneumococcal meningitis. PCV was introduced into the South African expanded programme on immunization (EPI) in 2009. Objective We evaluated the temporal association which the introduction of PCV into the South African EPI had on the incidence of pneumococcal meningitis in children. Methods The study was undertaken in Soweto. All children admitted to Chris Hani Baragwanath Academic Hospital (CHBAH) <14 years of age with meningitis from January 2006 to November 2011 were identified through an electronic database and their microbiological records reviewed to identify the causative bacteria. The results were time framed into two groups: prior to introduction of PCV 1 January 2006 to 31 March 2009 (pre-vaccine era) and post PCV-introduction 1 April 2009 to 30 November 2011 (post-vaccine era). Results 783 patients were admitted with suspected meningitis during the study period, of these 243 (31.0%) met the criteria for bacterial meningitis. The incidence of pneumococcal meningitis was decreasing in the CHBAH in-patient paediatric population by 4.7% per annum prior to the introduction of the vaccine in April 2009. The decline in incidence after PCV introduction accelerated to 18% per annum post-vaccine introduction (P=0.391). In the population most at risk for pneumococcal meningitis, children <1 year of age, the annual reduction in incidence of pneumococcal meningitis accelerated from 1.1% in the pre-vaccine era to 43.4% following PCV introduction (P= 0.011). Conclusions The introduction of PCV resulted in a decline in the incidence of pneumococcal meningitis in all age groups. This decline was most dramatic in the <1 year age group.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree Master of Medicine in Paediatrics (MMed) Johannesburg 2013
Keywords: Pneumococcal Vaccines; Meningitis